Case report: Sotrovimab, remdesivir and nirmatrelvir/ritonavir combination as salvage treatment option in two immunocompromised patients hospitalized for COVID-19 - Baldi, Federico; Dentone, Chiara; Mikulska, Malgorzata; Fenoglio, Daniela; Mirabella, Michele; Magnè, Federica; Portunato, Federica; Altosole, Tiziana; Sepulcri, Chiara; Giacobbe, Daniele Roberto; Uras, Chiara; Scavone, Graziana; et al. (Frontiers in Medicine, 2023)
COVID-19 in immunocompromised patients is difficult to treat. SARS-CoV-2 interaction with the host immune system and the role of therapy still remains only partly understood. There are no data regarding the use of monoclonal antibodies and the combination of two antivirals in fighting viral replication and disease progression. We report the cases of two patients, both treated with rituximab for non-Hodgkin lymphoma and granulomatosis with polyangiitis, respectively, and both hospitalized for COVID-19 with positive SARS-CoV-2 RNAemia, who were successfully treated with a salvage combination therapy with sotrovimab, remdesivir and nirmatrelvir/ritonavir.